The association of antihistamines and new-onset osteoarthritis in patients with autoimmune disease: a population-based cohort study - Chang, Chih-Feng; Chao, Tzu-Hsien; Huang, Jing-Yang; Liao, Pei-Lun; Yeh, Chih-Jung; Yang, Tsung-Yuan; Jong, Gwo-Ping (Frontiers in Immunology, 2026)
BackgroundAntihistamines have been reported to be linked with new-onset osteoarthritis (NOO). However, the effect of these drugs on NOO is unclear in patients with autoimmune disease. In this study, we aimed to investigate the effects of an antihistamine on NOO in patients with autoimmune disease.MethodsWe conducted a retrospective population-based cohort study involving patients who received antihistamines therapy and patients who did not receive antihistamines therapy. The outcome was the risk of NOO. We used multivariable Cox proportional hazard models to calculate the hazard ratios (HRs) and 95% confidence intervals (CIs) for the associations between antihistamines use and NOO.ResultsOverall, 49,078 patients who received antihistamines therapy and 196,312 patients who did not receive antihistamines therapy were matched for age, sex, and index date at a ratio of 1:4 between 2012 and 2022. During a follow-up of 9 years, 12,761 and 47,982 NOO events occurred in antihistamine users and nonusers, respectively. Antihistamine use was associated with a significantly higher risk of NOO (adjusted HR 1.05, 95% CI: 1.03–1.07, P < 0.0001). We confirmed the robustness of these results through a propensity score 1:1 matching analysis.ConclusionsIn this population-based cohort study, we found that antihistamine use was associated with a significantly increased risk of osteoarthritis in patients with autoimmune disease. Further efforts are needed to minimize the potential population drawbacks of these therapies in high-risk groups.